Prevalence of Eimeria spp in buffaloes in Mosul city - Baydaa AL-Lahaibi; Nadia Mohammed; Mostafa AL-Neema (مجلة الانبار للعلوم البيطرية, 2021)
The present study was conducted to estimate the prevalence of Eimeria sp . In buffalo from different regions of Mosul city included (Al-Kabat, Al-Shalalate, Badosh, Al-Rahmania) ,150 Fecal samples was examined form 2019-2020. The total infection rate was (38%) , five species were diagnosed; they are E.bovis 32%, E.subspherical 22.7% , E.zuerni 18.7% , E. ellipsoidalis 16.7% , E. auburnensis 6.7% . the study showed the higher infection rate by Eimeria bovis , The mixed infection with more than two species of Eimeria represented the highest rates and it was reported in 49.1%.The infection rate in the young animals(1-2 years) was higher (89.3) comparing to the rate in the a dult , according to the sex there is no significant difference between the male 33.3% and female 41.1% . histopathological examination characterized by emergence of different stages of parasite in the epithelium of intestinal, construction of intestinal gland cavities , severe hyperplasia of epithelial cell and presence of oedema between muscle fibers with infiltration with inflammatory cell .